Novel indirect approach to fabricating tissue engineering scaffolds - Tan, Jiayong (2011)
One of the key elements involved in the tissue engineering process is the scaffold which serves as a three-dimensional (3D) template for cell organization and tissue development. With the increasing number of studies demonstrating the profound influences of scaffold pore architecture on cell behavior and overall tissue growth, a scaffold fabrication method with sufficient architectural control becomes imperative. Yet, fabrication methods that are commonly employed today are rather inadequate in providing rigorous control over the entire scaffold pore architecture. More advance methods of fabrication such as rapid prototyping (RP) technologies, although having a higher degree of control over certain aspects of scaffold structure, are still unable to reliably produce micron-sized features due to resolution limitations. In the present study, an inverse method of scaffold fabrication which uses a lost-mold approach to form the architecture of the scaffold is proposed. By controlling the mold structure, the tissue engineer can have sufficient degree of macro- and micro-structural control over the scaffold architecture as the mold design would ultimately correspond to the negative replica of the entire scaffold pore structure. This thesis describes the developmental process of the inverse fabrication method which involves the use of two components: a mold produced from a RP fabricated template and microspheres.